Preparation and Characterization of Conductive Polyaniline/Silver Nanocomposite Films and Their Antimicrobial Studies. (17th October 2018) - Zengin, Huseyin; Aksin, Gulsen; Zengin, Gulay; Kahraman, Mehmet; Kilic, Ibrahim Halil
Abstract : Silver (Ag) nanoparticles are known to hold an important place in nanotechnology, and studies herein present the preparation and characterization of Ag metallic nanoparticles bearing antibacterial properties. In situ polymerization was used to prepare the conductive polymer polyaniline (PANI) and polyaniline/silver (PANI/Ag) nanocomposites. Increases in electrical conductivities of the nanocomposite films were observed compared to neat PANI, whereby these increases may be a result of the Ag doping effect or its complex formation. Spectroscopic techniques, such as, UV–Vis, FTIR, and photoluminescence were used for the characterizations of PANI and PANI/Ag nanocomposites. UV–Vis and FTIR data showed the quinoid units along the polymer chain being affected, such that strong interactions between Ag nanoparticles and quinoidal sites of PANI were presumed. The PANI/Ag nanocomposites showed higher photoluminescence intensities than neat PANI. TGA analyzes were used to determine weight losses and thermostabilities of PANI and PANI/Ag nanocomposites. Scanning electron microscopy was used for morphological evaluations of the nanoparticles and films, where the micrographs revealed that Ag nanoparticles were well dispersed and isolated in nanocomposite films. The presence and distribution of the Ag nanoparticles in PANI film matrix were analyzed by EDX. Antimicrobial properties of the nanocomposite films obtained were also explored. POLYM. ENG. SCI., 59:E182–E194, 2019. © 2018 Society of Plastics Engineers